Cytoplasmic overexpression, folding, and processing of penicillin acylase precursor in Escherichia coli - Xu, Y. L.; Hsieh, M. Y.; Narayanan, N.; Anderson, W. A.; Scharer, J. M.; Moo-Young, M.; Chou, C. P. (Biotechnology Progress, 2005)
Penicillin acylase (PAC) precursor, proPAC, was overproduced in a soluble or insoluble form in the cytoplasm of Escherichia coli through the expression of the leader-less pac gene (ll-pac) devoid of the coding region for the signal peptide of PAC. Also, a portion of the overexpressed proPAC was further processed to form mature PAC, indicating that the posttranslational processing steps for PAC maturation can occur in both the periplasm and the cytoplasm of E. coli. The cultivation performance for ll-pac expression was limited by several factors, including (1) misfolding of proPAC, resulting in the aggregation of insoluble proPAC as inclusion bodies, (2) intracellular proteolysis, leading to the degradation of the overexpressed gene products, and (3) inefficient PAC maturation, limiting the formation of active PAC. The effect of coexpression of various cytoplasmic chaperones, including trigger factor, GroEL/ES, DnaK/J-GrpE, and their combinations, on ll-pac expression was investigated. Intracellular proteolysis of the overexpressed gene products could be prevented by coexpression of GroEL/ES. On the other hand, coexpression of trigger factor appeared to be able to facilitate the folding of soluble proPAC and to improve PAC maturation. The roles of trigger factor and GroEL/ES could be coordinated to significantly improve ll-pac expression performance. DnaK/J-GrpE had an effect for solublization of proPAC and perhaps, similar to trigger factor, for improving PAC maturation. The ll-pac expression performance was also significantly improved through the simultaneous coexpression of DnaK/J-GrpE and GroEL/ES. The results of the study suggest that the folding and/or processing of proPAC could be a major issue limiting the overproduction of PAC in E. coli and the bottleneck could be eliminated through the coexpression of appropriate chaperone(s).